A Familiar Insight Into the use of Bibliometric Terms - Johnkennedy Nnodim; Onyeze Vitus; Ikem Promise Amarachi (Generasi Sains Indonesia, 2025)
This study investigates the relationship between traditional bibliometric indicators and altmetrics in evaluating scholarly impact across academic disciplines. The research aims to examine how citation metrics and online engagement collectively reflect research visibility and influence in the digital era. A quantitative bibliometric approach was employed using data collected from Scopus, Web of Science, Google Scholar, Altmetric, and PlumX databases. The analysis focused on citation counts, h-index, g-index, i10-index, and altmetrics engagement across multiple research fields. The findings revealed substantial disciplinary differences in citation performance, with natural sciences and health sciences demonstrating the highest citation visibility. The study also identified a positive relationship between citation counts and altmetrics, although several disciplines exhibited strong online engagement despite moderate citation levels. The novelty of this study lies in its integrated analytical framework that combines traditional citation analysis with alternative metrics to provide a multidimensional perspective of scholarly impact. The findings imply that research evaluation systems should incorporate both academic and societal dimensions to achieve more balanced and inclusive assessments of scientific contribution.